How to Overcome Anabolic Resistance in Dialysis-Treated Patients? - Garibotto, Giacomo; Saio, Michela; Aimasso, Francesca; Russo, Elisa; Picciotto, Daniela; Viazzi, Francesca; Verzola, Daniela; Laudon, Alessandro; Esposito, Pasquale; Brunori, Giuliano (Frontiers in Nutrition, 2021)
A current hypothesis is that dialysis-treated patients are “anabolic resistant” i.e, they have blunted stimulation of muscle protein synthesis rates (MPS) to common anabolic stimuli, an effect leading to muscle wasting and poor physical performance in ageing and in several chronic diseases. The importance of maintaining muscle mass and MPS is often underlooked in patients with dialysis-treated patients; better than to describe mechanisms leading to energy-protein wasting, the aim of this narrative review is to suggest possible strategies to overcome anabolic resistance in this patient’s category. The two major anabolic stimuli that augment MPS are food intake, in particular dietary protein, and physical activity. Unfortunately, dialysis patients are often aged and have a sedentary beheaviour, all condition which induce a state of “anabolic resistance” In addition, patients on dialysis are exposed to amino acid or protein deprivation during dialysis sessions. The optimal amount and formula of protein/amino acid composition in supplements to maximixe MPS is still unknown in dialysis patients. In young healthy subjects, 20 g whey protein maximally stimulate MPS. However, recent observations suggest that in dialysis patients greater amounts of proteins are needed to maximally stimulate MPS than in healthy subjects. Since unneccesary amounts of AA could stimulate ureagenesis, toxins and acid production, it is urgent to obtain information on the optimal dose of proteins or amino acids/ketoacids to maximize MPS in this patients’ population. In the meantime, the issue of maintaining muscle mass and function in dialysis-treated CKD patients needs not to be overlooked by the kidney community.